2004
DOI: 10.1111/j.1535-6841.2004.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Opportunities, Race, and Class: The Black Middle Class and Residential Segregation

Abstract: Racial residential segregation has received considerable attention from social scientists who, in general, have found that African Americans, particularly those in large, northeastern and midwestern metropolitan areas have been highly segregated from whites since at least the beginning of the Great Migration. This analysis combines research on racial residential segregation with research about residential segregation based on social class in order to study the segregation of middle‐class blacks from middle‐cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 51 publications
6
114
0
2
Order By: Relevance
“…Prior research has explored this issue primarily by examining levels of residential segregation of minorities from Anglos within income and education categories (e.g., Adelman 2004;Fischer 2003;Iceland, Sharpe, and Steinmetz 2005;Iceland and Wilkes 2006;Massey and Fischer 1999;St. John and Clymer 2000).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Prior research has explored this issue primarily by examining levels of residential segregation of minorities from Anglos within income and education categories (e.g., Adelman 2004;Fischer 2003;Iceland, Sharpe, and Steinmetz 2005;Iceland and Wilkes 2006;Massey and Fischer 1999;St. John and Clymer 2000).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Studies have also shown that, in general, minorities and lower-income people live closer to noxious land uses than do white and higher-income people. These social ills include proximity to waste dumps, superfund sites, incinerators, air pollution, traffic (Bullard, 2000;Crowder & Downey, 2010;Wing et al, 2000), food deserts (Wrigley et al, 2003;Zenk et al, 2005), fast-food chains (Boone-Heinonen et al, 2011;Kwate, 2008), social disorganization, crime, police surveillance and incarceration (Goffman, 2014;Sampson, 2012), and deteriorating and abandoned buildings (Adelman, 2004).…”
mentioning
confidence: 99%
“…No obstante, las cuestiones ecológicas no siguen teniendo gran importancia a la hora de explicar la segregación residencial, aunque persisten los elementos económicos, en los que se ha añadido en los últimos años, principalmente los ingresos de las personas (Adelman, 2004;Arjona, 2006; Comisión Económica para Amé-rica Latina y el Caribe, 2007;Hattery & Smith, 2005) y sus posibilidades de gasto o inversión en vivienda (Agostini, 2010;Therstrom & Therstrom, 1997;Zubrinsky & Bobo, 1996). De esta manera, los grupos con mayores rentas ocuparán lugares privilegiados, mientras que los de menor renta ocuparán los lugares menos deseados (Arjona y Checa, 2008;Echazarra, 2010;Sabatini, Cáceres y Cerda, 2000).…”
Section: Corrientes Explicativasunclassified